2017
DOI: 10.18632/oncotarget.16199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TLR-2/NF-κB signaling pathway on the occurrence of degenerative knee osteoarthritis: an in vivo and in vitro study

Abstract: The study aims to explore the effects of TLR-2/NF-κB signaling pathway on the occurrence of degenerative knee osteoarthritis (OA). Degenerative knee OA and normal cartilage samples were collected from patients with degenerative knee OA receiving total knee arthroplasty and amputation. Expressions of TLR-2, NF-κB and MMP-13 were determined by qRT-PCR and immunochemistry. The chondrocytes were divided into control, IL-1β, IL-1β + anti-TLR-2 and IL-1β + PDTC groups. MTT assay and flow cytometry were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 63 publications
5
27
0
Order By: Relevance
“…The causes of pathological alterations in synovitis include the release of proinflammatory cytokines and oxidative stress damage. Although a number of inflammatory factors, including tumor necrosis factor α (TNF-α), interleukin (IL)-1β, IL-18 and NACHT, LRR and PYD domains-containing protein 3 (NLRP3), are involved in the process of synovitis, there are few reports of small molecules that progressively degenerate articular synovial membrane in KOA (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The causes of pathological alterations in synovitis include the release of proinflammatory cytokines and oxidative stress damage. Although a number of inflammatory factors, including tumor necrosis factor α (TNF-α), interleukin (IL)-1β, IL-18 and NACHT, LRR and PYD domains-containing protein 3 (NLRP3), are involved in the process of synovitis, there are few reports of small molecules that progressively degenerate articular synovial membrane in KOA (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In chondrocytes, the most representative metalloproteases that degrade collagen and proteoglycans are MMP13 (matrix metalloproteinases 13) and ADAMTS5 (a disintegrin and metalloproteinase with thrombospondin motifs 5), respectively . The expression of these enzymes can be regulated by inflammatory factors and growth factors, such as TNF‐α, IL‐1β, TGF‐β and so on …”
Section: Introductionmentioning
confidence: 99%
“…During infection, TLR signaling is necessary for the proper activation of the body's immune response (22) TLRs produce a large amount of IL-1β and TNF-α in ammatory factors by activating the NK-κB in ammatory signaling pathway. Liu et al (23) found that the expression of TLR-2, NF-κB, MMP-13 and related in ammatory factors were signi cantly up-regulated with the severity of OA lesions, suggesting that TLR-2 / NF-κB signaling pathway may be involved in the occurrence of OA.…”
Section: Discussionmentioning
confidence: 99%